Left Atrial Electromechanical Remodeling Following 2 Years of High-Intensity Exercise Training in Sedentary Middle-Aged Adults. Issue 12 (19th March 2019) - McNamara, David A.; Aiad, Norman; Howden, Erin; Hieda, Michinari; Link, Mark S.; Palmer, Dean; Samels, Mitchel; Everding, Braden; Ng, Jason; Adams-Huet, Beverley; Opondo, Mildred; Sarma, Satyam; et al.
Abstract : Background: Moderate intensity exercise is associated with a decreased incidence of atrial fibrillation. However, extensive training in competitive athletes is associated with an increased atrial fibrillation risk. We evaluated the effects of 24 months of high intensity exercise training on left atrial (LA) mechanical and electric remodeling in sedentary, healthy middle-aged adults. Methods: Sixty-one participants (53±5 years) were randomized to 10 months of exercise training followed by 14 months of maintenance exercise or stretching/balance control. Fourteen Masters athletes were added for comparison. Left ventricular (LV) and LA volumes underwent 3D echocardiographic assessment, and signal-averaged electrocardiographs for filtered P-wave duration and atrial late potentials were completed at 0, 10, and 24 months. Extended ambulatory monitoring was performed at 0 and 24 months. Within and between group differences from baseline were compared using mixed-effects model repeated-measures analysis. Results: Fifty-three participants completed the study (25 control, 28 exercise) with 88±11% adherence to assigned exercise sessions. In the exercise group, both LA and LV end diastolic volumes increased proportionately (19% and 17%, respectively) after 10 months of training (peak training load). However, only LA volumes continued to increase with an additional 14 months of exercise training (LA volumes 55%; LV end diastolic volumes 15% at 24 months versus baseline; P <0.0001 for all). The LA:LV end diastolic volumes ratio did not change from baseline to 10 months, but increased 31% from baseline in the Ex group ( P <0.0001) at 24 months, without a change in controls. There were no between group differences in the LA ejection fraction, filtered P-wave duration, atrial late potentials, and premature atrial contraction burden at 24 months and no atrial fibrillation was detected. Compared with Masters athletes, the exercise group demonstrated lower absolute LA and LV volumes, but had a similar LA:LV ratio after 24 months of training. Conclusions: Twenty-four months of high intensity exercise training resulted in LA greater than LV mechanical remodeling with no observed electric remodeling. Together, these data suggest different thresholds for electrophysiological and mechanical changes may exist in response to exercise training, and provide evidence supporting a potential mechanism by which high intensity exercise training leads to atrial fibrillation. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT02039154. Abstract : Supplemental Digital Content is available in the text.